On the Origin of Sudden Slag Foaming During Copper Smelting - I. Bellemans; K. Verbeken; V. Cnockaert; T. Crivits (Canadian Institute of Mining, Metallurgy and Petroleum, 2019)
It is well known that slag foaming can significantly complicate copper smelting processes. This is especially true for unpredictable events that generate large amounts of slag foam during a small period of time. These events are here referred to as eruptions and are typical for certain types of liquid bath furnaces such as modern top submerged lance (TSL) furnaces. A few authors already made the link between over- oxidation of the slag phase and slag foaming. In this work, the mechanism is studied in more detail and explained using the smelter chemistry and the behaviour of dynamic foam formation. Finally, the most influential parameters on the foaming behaviour of the process are presented. INTRODUCTION Copper remains one of the most important metals used in our modern society. In 2017, the annual amount of copper produced worldwide was about 23.5 million metric tons. This makes copper the third most produced metal in the world after steel and aluminium. The majority of this copper was produced by copper smelting, about 19 million metric tons, both from primary concentrate and secondary feed material as reported in ICSG’s World Copper Factbook 2018. In the past, copper smelting was mainly performed using Flash smelting, a technology developed before 1949 (Kojo, Jokilaakso & Hanniala, 2000). Nowadays, this type of smelter is being complemented by other smelter types such as ISASMELT and Ausmelt technologies. These are two types op smelter furnaces, based on the concept of a top submerged lance (TSL) furnace. These two technologies were both commercialized around 1990 (Arthur & Hunt, 2005). It is estimated by Wang et al. (2016) that at this time, both flash and TSL smelters contribute equally to the total amount of annually smelted copper. Flash smelting stays the most important technology for extracting copper from primary sources. TSL furnaces, on the other hand, are more suited than Flash smelters for the recovery of copper from secondary materials. This is because of the different ways that the feed material is inserted in both furnaces. In Flash smelters, the ore and fluxes needs to be fine and completely dry in order to be able to blow the mixture inside the burner area of the furnace. The feed material for TSL smelters show less constrains concerning humidity and particle size. The material is dropped from the top inside the molten bath. As a result, a more complex and flexible feed stream can be processed using TSL smelting (Wood, Hoang & Hughes, 2017). This feature will become more important in the future as primary copper sources gets more scarce and the need for a fully sustainable material cycle increases.